T-DNA insertion mutants reveal complex expression patterns of the aldehyde dehydrogenase 3H1 locus in Arabidopsis thaliana - Missihoun, Tagnon D (Journal of experimental botany, 2012)
The Arabidopsis thaliana aldehyde dehydrogenase 3H1 gene (ALDH3H1; AT1G44170) belongs to family 3 of the plant aldehyde dehydrogenase superfamily. The full-length transcript of the corresponding gene comprises an open reading frame of 1583 bp and encodes a protein of 484 amino acid residues. Gene expression studies have shown that this transcript accumulates mainly in the roots of 4-week-old plants following abscisic acid, dehydration, and NaCl treatments. The current study provided experimental data that the ALDH3H1 locus generates at least five alternative transcript variants in addition to the previously described ALDH3H1 mRNA. The alternative transcripts accumulated in wild-type plants at a low level but were upregulated in a mutant that carried a T-DNA insertion in the first exon of the gene. Expression of the transcript isoforms involved alternative gene splicing combined with an alternative promoter. The transcript isoforms were differentially expressed in the roots and shoots and showed developmental stage- and tissue-specific expression patterns. These data support the hypothesis that alternative isoforms produced by gene splicing or alternative promoters regulate the abundance of the constitutively spliced and functional variants